NFAT5 Controls the Integrity of Epidermis - Muhammad, Khalid; Xavier, Delicia; Klein-Hessling, Stefan; Azeem, Muhammad; Rauschenberger, Tabea; Murti, Krisna; Avots, Andris; Goebeler, Matthias; Klein, Matthias; Bopp, Tobias; Sielaff, Malte; Tenzer, Stefan; et al. (Frontiers in Immunology, 2021)
The skin protects the human body against dehydration and harmful challenges. Keratinocytes (KCs) are the most abundant epidermal cells, and it is anticipated that KC-mediated transport of Na+ ions creates a physiological barrier of high osmolality against the external environment. Here, we studied the role of NFAT5, a transcription factor whose activity is controlled by osmotic stress in KCs. Cultured KCs from adult mice were found to secrete more than 300 proteins, and upon NFAT5 ablation, the secretion of several matrix proteinases, including metalloproteinase-3 (Mmp3) and kallikrein-related peptidase 7 (Klk7), was markedly enhanced. An increase in Mmp3 and Klk7 RNA levels was also detected in transcriptomes of Nfat5-/- KCs, along with increases of numerous members of the ‘Epidermal Differentiation Complex’ (EDC), such as small proline-rich (Sprr) and S100 proteins. NFAT5 and Mmp3 are co-expressed in basal KCs of fetal and adult skin but not in skin of newborn (NB) mice. This is correlated with a strong increase in Mmp3 and Klk7 expression in KCs of NB mice and suggests, along with the fragile epidermis of adult Nfat5-/- mice, a suppressive effect of NFAT5 on the expression of matrix proteases in skin. Our data suggest a role of NFAT5 in controlling the generation of matrix proteases in skin that contribute to the manifold changes during embryonal skin development and skin integrity in adults.